Makna Upacara Nyaki Tihi Adat Dayak Ngaju di Desa Samba Danum Katingan, Kalimantan Tengah - Wilson, Wilson (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2009)
Dayak is an ethnic group lived at Kalimantan which used to be called as Borneo. From some resources stated that Dayak come from Proto-Malay Group which was at India. They come to Borneo across Malaya Peninsula about 4000 years ago. Dayak group respect their previous customs. This research is aimed at one of custom that still exist at Dayak Community Ngaju group lived at Samba Danum Katingan Yillage, the custom is "Nyaka Tihi" which has sociologies, physiologies, and religius meaning that affect their life.